Effects of Parental Death on Labor Market Outcomes - Jensen, Mathias Fjællegaard; Zhang, Ning (American Economic Review, 2026)
We use Danish administrative data to examine the effects of parental death on labor market outcomes. Leveraging the timing of sudden, first parental deaths and a matched-control difference-in-differences strategy, we find that men’s earnings decline by 2 percent, while women’s earnings decline by 3 percent following a parental death. Both women and men experience mental health deterioration, leading to increased use of psychological assistance and prescriptions for mental health conditions and opioids. Women with young children experience a comparatively larger earnings decline (around 4 percent) likely due to the loss of informal childcare. (JEL D91, I12, J13, J16, J31)